Design and Implementation of a Runtime System for Parallel Numerical Simulations on Large-Scale Clusters - Schliephake, Michael; Aguilar, Xavier; Laure, Erwin (Procedia computer science, 2011)
The execution of scientific codes will introdu ce a number of new challenges and intensify some old ones on new high-performance computing infrastructures. Petascale computers are large systems with complex designs using heterogeneous technologies that make the programming and porting of applications difficult, particularly if one wants to use the maximum peak performance of the system. In this paper we present the design and first prototype of a runtime system for parallel numerical simulations on large-scale systems. The proposed runtime system addresses the challenges of performance, scalability, and programmability of large-scale HPC systems. We also present initial results of our prototype implementation using a molecular dynamics application kernel.